Asymmetric cryptosystem and software design based on two-step phase-shifting interferometry and elliptic curve algorithm - Fan, Desheng; Meng, Xiangfeng; Wang, Yurong; Yang, Xiulun; Peng, Xiang; He, Wenqi; Dong, Guoyan; Chen, Hongyi (Optics communications, 2013)
We propose an asymmetric cryptosystem based on two-step phase-shifting interferometry (PSI) and elliptic curve (EC) public-key cryptographic algorithm, in which one image is encrypted to two interferograms by double random-phase encoding (DRPE) in Fresnel domain and two-step PSI, and the session keys such as geometrical parameters and pseudo-random seeds, are asymmetrically encoded and decoded with the aid of EC algorithm. The receiver, who possesses the corresponding private key generated by EC algorithm, can successfully decipher the transmitted data using the extracted session keys. The utilization of EC asymmetric cryptosystem solves the problem of key management and dispatch, which is inevitable in the conventional optical symmetric cryptosystems. Not only computer simulation, but also software design and development are carried out to verify the feasibility of the proposed cryptosystem.